Computer Vision in Medical Imaging Detecting Tumors Using AI-Powered Image Processing - Dr.S.Omprakash; Mrs.K.R.Prabha; Mrs.P. Shanthi; Dr.K.Santhi; Dr.M.Sangeetha (The Bioscan, 2025)
This research describes how computer vision applies to medical imaging through the discussion of automated AI techniques in addition to their limitations. The research demonstrates that CNNs among deep learning algorithms enhance tumor detection accuracy effectively. The available technology faces current issues related to data availability as well as understanding technical processes. This research examines how AI technology can improve healthcare diagnosis procedures along with its prospective path of advancement.